2014
DOI: 10.1039/c3cc48738e
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of 2-amino-substituted BODIPYs providing pyrazine-fused BODIPY trimers

Abstract: Oxidation of 2-amino-substituted BODIPYs afforded BODIPY trimers in a one-step operation. The trimer consists of a pyrazine-fused BODIPY dimer to which one BODIPY unit is connected through an NH linkage. Effective expansion of π-conjugation over the fused dimer was observed in optical and electrochemical measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 16 publications
(1 reference statement)
0
12
0
1
Order By: Relevance
“…Various structural modifications on BODIPY have been summarized to obtain far-red and NIR derivatives, 2 mainly by introducing linear aromatic groups, 4 cyclic aromatic groups, 5 N replacing meso-C 6 and conjugated oligomers. [7][8][9] Recently, several BODIPY conjugated oligomers with fused structures have been synthesized showing intensive NIR absorption/ emission bands due to the expansion of p-conjugation. Wakamiya and Yamaguchi 7 developed a,a-benzene fully fused bisBODIPY A (Fig.…”
mentioning
confidence: 99%
“…Various structural modifications on BODIPY have been summarized to obtain far-red and NIR derivatives, 2 mainly by introducing linear aromatic groups, 4 cyclic aromatic groups, 5 N replacing meso-C 6 and conjugated oligomers. [7][8][9] Recently, several BODIPY conjugated oligomers with fused structures have been synthesized showing intensive NIR absorption/ emission bands due to the expansion of p-conjugation. Wakamiya and Yamaguchi 7 developed a,a-benzene fully fused bisBODIPY A (Fig.…”
mentioning
confidence: 99%
“…[53] This protocol has been applied to 2-amino-BODIPYs 39 to produce BODIPY trimers 40 containing ap yrazineu nit in sufficient yield (Scheme20c). [54] Another example of the oxidative coupling of aromatic amines has been reported by He and co-workers (Scheme 21). [55] They prepared p-extended triphenylenes 42 by oxidation of amino-substituted triphenylene 41.I nt his case, they used molecular oxygen alonea sa no xidantf or this coupling reaction.…”
Section: Intermolecular Cànbond-forming Reactions To Form Phenazinedementioning
confidence: 94%
“…In addition, they reported that this protocol works with 2‐amino‐9,10‐disubstituted anthracene derivatives 37 , providing the corresponding dimers 38 (Scheme b) . This protocol has been applied to 2‐amino‐BODIPYs 39 to produce BODIPY trimers 40 containing a pyrazine unit in sufficient yield (Scheme c) …”
Section: Intermolecular Covalent Bond Formation Through Oxidation Of mentioning
confidence: 99%
“…Therefore, nitration reaction is one of the first choices for further derivatization of aromatic compounds. Recently, large π-conjugated materials with a nitro group and their derivatives have attracted continuing attention from many research areas [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%